MORAL PRINCIPLES IN THE LEGACY OF 18TH-19TH CENTURY THINKERS (Scientific journal of the Fergana State University, 2026)
This article analyzes the socio-political and ethical views of Eastern thinkers. In particular, it examines the socio-political rise of Turkestan during the 9th–12th and 14th–15th centuries, as well as the factors contributing to its decline in the 18th–19th centuries from the perspective of political philosophy. The intellectual legacy of prominent scholars such as Khoja Samandar Termizi, Sufi Allayar, Mirzo Abdulqadir Bedil, Ahmad Donish, Ogahiy, Furqat, and Zavqiy is explored, emphasizing their views on leadership ethics, justice, and the stability of society as valuable sources for understanding contemporary issues. The study highlights the significance of justice, morality, the unity of knowledge and thought, as well as the role of essential values in ensuring social harmony and human progress. This scholarly analysis underscores the relevance of this historical legacy for modern political and philosophical research.